The enigma of life: confronting marvels at the edges of science. Issue 1 (16th June 2020) - Paulson, Steve; Gleiser, Marcelo; Lombrozo, Tania; Francis, Gavin
Abstract: Einstein famously claimed that "the most incomprehensible thing about the universe is that it is comprehensible." This statement suggests that no amount of scientific explanation will suffice to make sense of the bizarre situation of the human mind within the universe. So what are the actual roles of awe and wonder within the framework of contemporary science? How, for instance, do awe and wonder inform scientists' understanding of the phenomena they are researching? What aspects of contemporary science are more likely to elicit wonder, and why? Is science rechanneling our innate thirst for knowledge and understanding toward more concrete and palpable realities, or is it aggravating the tension between truth and meaning by revealing the scope of our ignorance when it comes to probing the ultimate nature of reality? Physicist Marcelo Gleiser, experimental psychologist Tania Lombrozo, and physician Gavin Francis analyze the impact of awe and wonder on their own work and on the mindsets of their colleagues carrying out leading‐edge scientific research.